Greater experience in the treatment of hypoplastic uterus with the cervix estrogen - De la Puente Lanfranco, Rafael (2015)
The author presents his experience in the treatment of uterine hypoplasic with local injections of estradiol. His group was formed by 66 patients suffering of sterility; the mean age was 29 years; 78 % of the cases had primary sterility, 19% were of the secondary type and 3% corresponded to infertility. After the treatment was completed there were 19 pregnancies, this is 28,7 %. The best results were obtained in primary sterility and discrete hypoplasia of the uterus. 27 % of the cases presented some side effects that were well tolerated. The author believes that some cases of sterility due to hypoplasia of the uterus can be treated succesfully with local injections of estradiol.